The relationship between technostress and job satisfaction among non-executive staff at Jabatan Tanah dan Survei, Kota Samarahan / Sara Safwah Ismail - Ismail, Sara Safwah (2018)
Achieving higher employees’ job satisfaction is the main focus of most organizations. However, the issue of technostress toward job satisfaction has been long debated. This research investigated the correlation between technostress and job satisfaction at Jabatan Tanah dan Survei, Kota Samarahan. There are three objectives for the study. The objectives of the research were; to investigate the relationship between techno-overload and job satisfaction, to determine the relationship between techno-uncertainty and job satisfaction and to identify the relationship between techno-complexity and job satisfaction among non executive staff at Jabatan Tanah dan Survei. The literature review was done by using the conceptual framework as adapted for analysis. The data were collected by using questionnaires. Convenience sampling technique was used to select respondents and the questionnaires has been distributed to 92 respondents. Data analysis involved correlations coefficient. The findings of this study indicates weak relationship between technostress and job satisfaction at Jabatan Tanah dan Survei Kota Samarahan. r= -0.140 were techno-overload, r=0.120 were techno-uncertainty and r=-0.192 were techno-complexity. It can be concluded that technostress creators which included techno-overload, techno-uncertainty and techno-complexity have a little influence on the job satisfaction of non-executives staff at Jabatan Tanah dan Survei Kota Samarahan. The study recommends that the organization has to provide appropriate tasks or works for employees that may need them to finish it by using technology in order to prevent the employees to feel stress when using that technology. As for the future researcher, this study may be used as a reference for them to conduct technostress research towards job satisfaction.